Pedunculopontine Nucleus Gamma Band Activity-Preconscious Awareness, Waking, and REM Sleep - Urbano, Francisco J.; D’Onofrio, Stasia M.; Luster, Brennon R.; Beck, Paige B.; Hyde, James Robert; Bisagno, Veronica; Garcia-Rill, Edgar (Frontiers in Neurology, 2014)
The pedunculopontine nucleus (PPN) is a major component of the reticular activating system (RAS) that regulates waking and REM sleep, states of high frequency EEG activity. Recently, we described the presence of high threshold, voltage-dependent N- and P/Q-type calcium channels in RAS nuclei that subserve gamma band oscillations in the mesopontine pedunculopontine nucleus (PPN), intralaminar parafascicular nucleus (Pf), and pontine Subcoeruleus nucleus dorsalis (SubCD). Cortical gamma band activity participates in sensory perception, problem solving, and memory. Rather than participating in the temporal binding of sensory events as in the cortex, gamma band activity in the RAS may participate in the processes of preconscious awareness, and provide the essential stream of information for the formulation of many of our actions. That is, the RAS may play an early permissive role in volition. Our latest results suggest that, 1) the manifestation of gamma band activity during waking may employ a separate intracellular pathway compared to that during REM sleep, 2) neuronal calcium sensor (NCS-1) protein, which is over expressed in schizophrenia and bipolar disorder, modulates gamma band oscillations in the PPN in a concentration-dependent manner, 3) leptin, which undergoes resistance in obesity resulting in sleep dysregulation, decreases sodium currents in PPN neurons, accounting for its normal attenuation of waking, and 4) following our discovery of electrical coupling in the RAS, we hypothesize that there are cell clusters within the PPN that may act in concert. These results provide novel information on the mechanisms controlling high frequency activity related to waking and REM sleep by elements of the RAS.